The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1108/oir-07-2016-0185
|View full text |Cite
|
Sign up to set email alerts
|

Social networking for scientists: an analysis on how and why academics use ResearchGate

Abstract: Purpose The purpose of this paper is to examine the usage and utility of ResearchGate (RG), which is a social networking site where scientists disseminate their work and build their reputations. In a sample consisting largely of American and European academics, the authors analyzed the ways they use the site, what they thought about the site’s utility, and the effects of usage on career outcomes. Design/methodology/approach The authors employed an online survey approach to target scientists who have an activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 21 publications
(17 reference statements)
5
59
0
4
Order By: Relevance
“…In line with the recommendations of Williams and Woodacre (2016), our work focuses on the features and characteristics of specific sites. Although academic engagement on social media takes place on a wide range of SNS (Nentwich and König, 2014), most research has focused on a single platform such as Facebook (Sharma, et al, 2016), Twitter (Knight and Kaye, 2016;Veletsianos and Kimmons, 2016), Academia.edu (Thelwall and Kousha, 2014), or ResearchGate (Muscanell and Utz, 2017).…”
Section: Justificationmentioning
confidence: 99%
“…In line with the recommendations of Williams and Woodacre (2016), our work focuses on the features and characteristics of specific sites. Although academic engagement on social media takes place on a wide range of SNS (Nentwich and König, 2014), most research has focused on a single platform such as Facebook (Sharma, et al, 2016), Twitter (Knight and Kaye, 2016;Veletsianos and Kimmons, 2016), Academia.edu (Thelwall and Kousha, 2014), or ResearchGate (Muscanell and Utz, 2017).…”
Section: Justificationmentioning
confidence: 99%
“…One of the largest ASNSs is ResearchGate, which includes a Q&A platform through which scholars can communicate by posing academic questions and providing answers. However, prior studies have found that scholars' engagement with ASNSs is lower than that with other types of social media (Muscanell & Utz, 2017). This is reflected in the low response quantity for many questions on Research-Gate Q&A.…”
Section: Introductionmentioning
confidence: 94%
“…Sharing work and enhancing citations also emerged as the highest priorities within a larger-scale online survey about ResearchGate use (Muscanell and Utz, 2017). The survey data were also analyzed to examine links between site use and career progression; no links were found, although the data indicated links to stress and productivity (Muscanell and Utz, 2017).…”
Section: User Perspectivesmentioning
confidence: 99%
“…Sharing work and enhancing citations also emerged as the highest priorities within a larger-scale online survey about ResearchGate use (Muscanell and Utz, 2017). The survey data were also analyzed to examine links between site use and career progression; no links were found, although the data indicated links to stress and productivity (Muscanell and Utz, 2017). To focus in on this issue, Utz and Muscanell (2018) present a related study which examined links between emotions and observing ResearchGate metrics, based on 419 responses to an online survey.…”
Section: User Perspectivesmentioning
confidence: 99%